Barriers and Facilitators to Seeking Sleep Solutions for Children With Cerebral Palsy: A Qualitative Study - Petersen, Sacha; Reddihough, Dinah S.; Lima, Sally; Harvey, Adrienne; Newall, Fiona (Frontiers in Psychiatry, 2021)
Background: Published evidence to date suggests that sleep problems are common in children with cerebral palsy (CP). This qualitative study is a follow up to a previously published quantitative phase on the experience and impact of sleep problems in this population. Aims: The aim of this study was to explore the experience and impact of sleep disturbance and seeking of sleep solutions for parents of school aged children with CP. Materials and Methods: Semi-structured 19 qualitative interviews were conducted with parents of children with CP aged 6–12 years. Interview data were transcribed verbatim and the thematic analysis techniques by Braun and Clarke was used to identify themes. Results: Thematic analysis identified 7 themes: (1) My Child Doesn't Fit into the Box, (2) A Mother's Ears are Always On, (3) Sleep Disturbance is like Water Torture, (4) Sleep is One of Many Spot Fires, I Put it on the Backburner, (5) Luck, Money or Jumping Up and Down, (6) There is Never One Silver Bullet and (7) Help: The Earlier the Better. The key finding was that parents of children with CP often described their child's needs being distinct from what is provided by systems and services. Conclusion: Parents face significant challenges sourcing effective sleep solutions for their child with CP. Sleep is often not a priority for either the parent or the clinician as other health problems take precedence. Parents reflected that early sleep intervention for their child was or would have been helpful. The barriers and facilitators to sleep care identified in this study should be used to inform clinical change in care for children with CP. Sleep needs to be prioritized in healthcare for children.